The social role of the Museum: a visitor survey in the Cape - Van Zyl, Cornelia Christina (Department of Historical Studies, 2015)
The origin of the term "museum" can be traced back to Ancient Greece where it was applied to a temple for the adoration of the Muses. By the end of the 3rd century A. D. such museums had perished and the term "museum" was not used again until the 16th century when it was applied to the private collections which developed in Italy and then spread through Europe. These private collections were the direct forerunners of the public museum; during the late 17th and 18th centuries many of the private collections were opened to the public and by the 19th century the main functions of these museums were seen as being collection, research and education. At the time the museums gave little attention to actively fulfilling these functions and to serving the public. Subsequently the museums were held in low esteem by the public. In many countries this trend persisted .until after the second world war for only then a real understanding and appreciation of the value and role of museums came about. Many museums started reconsidering their aims and position in society, reforming and incorporating all manifestations of change in the communities which they had to serve. Many museums started working toward becoming more dynamic institutions involved with their respective communities. In this striving toward community involvement the avenues of involvement have been examined in detail but there have been few attempts to learn anything about the communities served by museums. In most cases museum policy is based on personal convictions as to who the public is, what they want, need and deserve, instead of being based on quantitative information. A number of surveys of museum visitors and the non-visitors have been carried out overseas in an attempt to get to know more about the communities served by museums. In South Africa there is almost a total lack of such information as most museums have been too busy with their own internal problems to go through the trouble of learning something about the communities they serve. Considering this lack of information in South Africa a survey of museum visitors was carried out in an attempt to obtain some factual and objectively trustworthy information on one section of the communities served by the museums. 36 Museums in the Cape Province took part in the survey and 6664 visitors completed the multiple-choice questionnaire.